OBESITY AND OUTCOME AMONG PATIENTS HOSPITALIZED SARS-COV-2: A HOSPITAL-BASED STUDY IN INDONESIA: Obesity and Outcome among Patients Hospitalized SARS-CoV-2 - MASRUL, Masrul; USMAN, Elly; FEBRI , Dewi Susanti (African Journal of Infectious Diseases (AJID), 2023)
Background: Patients with obesity who have SARS-CoV-2 are at significant risk for developing serious clinical problems that need intensive care and have a bad prognosis. Aim: The aim of this study was to determine obesity and outcome among patients hospitalized SARS-CoV-2 at Indonesia's national referral hospital. Methods: This study used a retrospective cohort. The research sample was SARS-CoV-2 patients who were treated by pulmonary specialists in the intensive room of Dr. M. Djamil Hospital Padang. The number of samples in this study was 106 subjects. Data analysis was performed using the Chi-square test, Kaplan-Meier, and Cox regression. P < 0.05 was significant, and the data were analyzed using the SPSS version 21.0 program. Results: The results of this study found obesity was associated with the outcome of SARS-CoV-2 patients treated at Indonesia's national referral hospital (p<0.05, OR=3.55 (95% CI 1.44-8.71)). The mortality rate among patients hospitalized with SARS-CoV-2 at Indonesia's national referral hospital with obesity was higher than non-obese, namely 82.7% and 57.4%. The length of stay in patients with obesity was also shorter, namely 12 days compared to 19 days in non-obese. Conclusion: There was an association between obesity with mortality of SARS-CoV-2 patients in a national referral hospital Indonesia. This study can provide input in the therapeutic management of patients with obesity so as to reduce the poor prognosis.